Intercellular signaling across plasmodesmata in vegetable species - Meng Li; Xufang Niu; Shuang Li; Qianfang Li; Shasha Fu; Chunhua Wang; Shuang Wu (Vegetable Research)
The formation of edible organs and stress adaption are two major focuses of the studies on vegetable species. The regulation of these two processes often involves cell-to-cell signaling. In most plants, including vegetable species, intercellular signaling can be delivered by mobile regulators that traffic through a channel called plasmodesmata connecting almost all cells. A large number of transcription factors and RNAs have been discovered to move across plasmodesmata (called the symplastic way) to travel a short-range or a long-distance. This symplastic transport of signaling molecules has emerged to be an important regulation of a wide range of developmental and physiological processes. Callose deposition to plasmodesmata is a key step controlling the plasmodesmata permeability in many cell types. Here we summarize the recent progress in our understanding of plasmodesmata-mediated signaling in plants.